The spectrum of Charcot-Marie-Tooth disease due to myelin protein zero: An electrodiagnostic, nerve ultrasound and histological study. Issue 1 (January 2018) - Fabrizi, Gian Maria; Tamburin, Stefano; Cavallaro, Tiziana; Cabrini, Ilaria; Ferrarini, Moreno; Taioli, Federica; Magrinelli, Francesca; Zanette, Giampietro
Highlights: Nerve ultrasound with neurophysiology and pathology enlarged the perspective on MPZ -related CMT. Traditional NCS criteria are limited in describing the whole spectrum of MPZ -related CMT. Nerve ultrasound may have diagnostic value for CMT1B vs. other demyelinating peripheral neuropathies. Abstract: Objective: Nerve ultrasound (US) data on myelin protein zero ( MPZ )-related Charcot-Marie-Tooth disease (CMT) are lacking. To offer a comprehensive perspective on MPZ -related CMTs, we combined nerve US with clinics, electrodiagnosis and histopathology. Methods: We recruited 36 patients (12 MPZ mutations), and correlated nerve US to clinical, electrodiagnostic measures, and sural nerve biopsy. Results: According to motor nerve conduction velocity (MNCV) criteria, nine patients were categorized as "demyelinating" CMT1B, 17 as "axonal" CMT2I/J, and 10 as dominant "intermediate" CMTDID. Sural nerve biopsy showed hypertrophic de-remyelinating neuropathy with numerous complex onion bulbs in one patient, de-remyelinating neuropathy with scanty/absent onion bulbs in three, axonal neuropathy in two, mixed demyelinating-axonal neuropathy in five. Electrodiagnosis significantly differed in CMT1B vs. CMT2I/J and CMTDID subgroups. CMT1B had slightly enlarged nerve cross sectional area (CSA) especially at proximal upper-limb (UL) sites. CSA was negatively correlated to UL MNCV and not increased at entrapment sites. Major sural nerve pathological patterns were uncorrelated to UL nerve US and MNCV. Conclusions: Sural nerve biopsy confirmed the wide pathological spectrum of MPZ-CMT. UL nerve US identified two major patterns corresponding to the CMT1B and CMT2I/J-CMTDID subgroups. Significance: Nerve US phenotype of MPZ -CMT diverged from those in other demyelinating peripheral neuropathies and may have diagnostic value.